“Norms” as the noumenon, “functions” for use: A new idea of cultivated land administrative protection in China - Li, Lingling; Gao, Haoran; Cui, Caixian (Frontiers in Environmental Science, 2023)
In the 70 years since it has been founded, China's cultivated land protection work has made remarkable achievements: less than 10% of the world's cultivated land has fed 22% of the world's population and 900 million peasants have the foundation on which to survive and develop. However, under the strictest protection system such as "Grow Teeth" (GT), there is still a deviation of "norm-value" and "demand-efficacy" in the Administrative Protection of Cultivated Land (APCL) at this stage. This paper uses normative analysis method, similar case research method as well as value analysis method to find that the legitimacy of the current APCL system is insufficient: on the one hand, under the perspective of functionalist "needs and efficacy", the existing Cultivated Land Protection Law (Draft) (CLPL) and other normative documents cannot meet the needs of APCL penalties, relief, public welfare, etc.; On the other hand, from the perspective of normative "value legitimacy", APCL legitimacy value foundation is lacking due to the limitations of overall value fragmentation, insufficient compatibility value and fragile defensive value. Therefore, the value base of APCL should be dismantled under the guidance of "function for use" to disassemble the functions of punishment, relief and public welfare, so as to specifically realize the construction of CLPL subjects, the inheritance of regulations, the transformation of responsibility subdivision, and the Land Administration Law (LAL) and other regulatory continuations, , to carry out protective measures such as clarifying the scope of punishment and giving compulsory force after coordination to cultivated land protection inspection recommendations, so as to give full play to the efficacy of APCL.